2018
DOI: 10.1007/s10943-018-0732-x
|View full text |Cite
|
Sign up to set email alerts
|

The Pornography Debate: Religiosity and Support for Censorship

Abstract: Pornography has become an increasingly salient topic in public discourse. We sought to better understand the role of religiosity in shaping people's support of policy stances against pornography, in the form of censorship, using nationally representative data from the 2014 General Social Survey (n = 1676). Results from logistic regression indicate that high religiosity significantly increases odds of supporting censorship. Holding control variables at their sample means, the least religious persons had a predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Likewise, religious makeup of the current sample was unique. Our results, however, are congruent with findings from a previous study that utilized nationally representative data (Droubay et al, 2018) on support of policy stances against pornography (i.e., censorship); that study further suggested that strength of religious faith (i.e., religiosity) is more important than actual religious affiliation in predicting support for antipornography laws, at least among Western, Christian faith adherents.…”
Section: Limitationssupporting
confidence: 90%
See 2 more Smart Citations
“…Likewise, religious makeup of the current sample was unique. Our results, however, are congruent with findings from a previous study that utilized nationally representative data (Droubay et al, 2018) on support of policy stances against pornography (i.e., censorship); that study further suggested that strength of religious faith (i.e., religiosity) is more important than actual religious affiliation in predicting support for antipornography laws, at least among Western, Christian faith adherents.…”
Section: Limitationssupporting
confidence: 90%
“…Control variables. Pornography consumption was included as a control variable, as past literature indicates consumers are less apt to endorse censorship of it (Droubay et al, 2018;Gunther, 1995); thus, it is possible that pornography viewership affects persons' attitudes about whether it is addictive and a public health concern. Respondents were asked how frequently they intentionally viewed pornography in the past year; responses were dichotomized into pornography consumers and non-consumers (0 ¼ no, 1 ¼ yes).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although religiosity and moral disapproval significantly predicted moral incongruenceerelated distress, their contribution was somewhat limited. Other possible predictors should be investigated, both connected to other sources of norms that can determine disapproval of pornography, for example, sociopolitical views, religious fundamentalism 53,54 or certain branches of feminism, 55 as well as variables related to the awareness and sensitivity to own behaviors being incongruent with own beliefs, attitudes, and internalized norms (eg, self, awareness, concern over mistakes, perfectionism, the centrality of the norms that motivate attitudes toward pornography and sexuality). Here, we echo the suggestions that were voiced by other authors in their commentaries for the model.…”
Section: Moral Incongruence Pathmentioning
confidence: 99%
“…Religious belief and practice have demonstrated particularly strong associations with moral disapproval of pornography use (for a review, see Grubbs, Perry, et al, 2019). Over both remote (Lambe, 2004) and recent (Droubay, Butters, & Shafer, 2018) studies, the belief that pornography use is a moral evil is extremely well predicted by religiousness. These findings are underscored by qualitative sociological work that demonstrated a uniquely religious element in antipornography sentiments over the past half-century (Thomas, 2013, 2016).…”
Section: Controversies Surrounding Csbd and Pornography Usementioning
confidence: 99%